Cloning of gene encoding the vegetative insecticidal protein (Vip3) from Bacillus thuringiensis - Ngọc, Phạm Bích; Ngọc, Lê Thị Hồng; Trà, Phạm Thị; Hà, Chu Hoàng; Bình, Lê Trần (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 99-104, 2005